2013
DOI: 10.1103/physrevb.87.115419
|View full text |Cite
|
Sign up to set email alerts
|

Weak and strong coupling regimes in plasmonic QED

Abstract: We present a quantum theory for the interaction of a two level emitter with surface plasmon polaritons confined in single-mode waveguide resonators. Based on the Green's function approach, we develop the conditions for the weak and strong coupling regimes by taking into account the sources of dissipation and decoherence: radiative and non-radiative decays, internal loss processes in the emitter, as well as propagation and leakage losses of the plasmons in the resonator. The theory is supported by numerical cal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
157
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(161 citation statements)
references
References 90 publications
(139 reference statements)
1
157
0
Order By: Relevance
“…Similar nano-antennas were considered in a later work [200] where strong coupling was also also predicted. In [201] various plasmonic waveguide structures were considered for single emitter strong coupling, it was concluded that cryogenic temperatures would be needed to observe strong coupling. The results of this work [201] also suggest the need for nanostructures with very small dimensions and sharp features to provide small enough mode volumes for room temperature single emitter strong coupling.…”
Section: Conclusion Open Questions and Future Directionsmentioning
confidence: 99%
“…Similar nano-antennas were considered in a later work [200] where strong coupling was also also predicted. In [201] various plasmonic waveguide structures were considered for single emitter strong coupling, it was concluded that cryogenic temperatures would be needed to observe strong coupling. The results of this work [201] also suggest the need for nanostructures with very small dimensions and sharp features to provide small enough mode volumes for room temperature single emitter strong coupling.…”
Section: Conclusion Open Questions and Future Directionsmentioning
confidence: 99%
“…This result is naturally obtained in the standard DLN approach [29,40] and therefore constitutes another illustration of the powerfulness of the DLN methodology (see refs. [37][38][39][40][41][42][43][44][45] for more on this topics in connection with Bloch equations and the DLN formalism). Moreover, in the present article we showed how to give a clean foundation to the DLN approach by including dipolar sources located far away from the dipole µ 1,2 and its local environment and acting effectively as the pure photon field required in the generalized Huttner-Barnett formalism [71,72] (see also [17]).…”
Section: B Some Important Consequences: Spontaneous Emission Fluctumentioning
confidence: 99%
“…Instead, fluctuating currents are phenomenologically added to deal with the problem of dissipation and dispersion. This approach was intensively used in the literature [27][28][29][30][31][32][33][34][35][36], e. g., for describing optical Bloch equations in the weak or strong optical coupling in QNP [37][38][39][40][41][42][43][44][45], Casimir interactions, quantum frictions and thermal fluctuating forces [46][47][48][49][50], and more recently for modeling quantum optical non-linearities such as spontaneous down conversion of photon pairs [51,52]. It is central to observe that the DLN approach is a direct development of the historical works by Rytov and others [53][54][55][56] which, based on some considerations about the standard fluctuation dissipation theorem for electric currents [57], was used for justifying Casimir and thermal forces (for recent developments of such phenomenological 'fluctuational electrodynamics' techniques in the context of nanotechnology see [58][59][60][61][62][63]).…”
Section: Introductionmentioning
confidence: 99%
“…In order to further investigate the weak and strong coupling regimes, we will analyze the dependence of the coupling constant g on the various parameters involved, namely the value of the chemical potential μ, the emission frequency of the QE ω, and the distance of the QE to the GM z. Considering ω = ω SP , i.e., zero detuning, the criterion for having strong coupling is whether or not the absorption spectrum of the system exhibits two peaks of different frequencies [40,41]. This condition is fulfilled if…”
Section: B Rabi Splitting-strong Coupling Regimementioning
confidence: 99%